2017
DOI: 10.1177/1541931213601636
|View full text |Cite
|
Sign up to set email alerts
|

The Usability of Blood Glucose Meters: Task Performance Differences Between Younger and Older Age Groups

Abstract: This study examines the overall usability of current, commercially available self-monitoring blood glucose (SMBG) meters in order to highlight how the design affects the performance of younger and older adults. Sixteen younger participants (18-27) and 29 elderly participants (65-85) attempted to complete two tasks: 1) set date/time and 2) perform a control solution test, using two meters: the Accu-Check Compact Plus® and 2) the One Touch Ultra 2®. Overall, elderly participants had significantly more difficulty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 18 publications
3
7
0
Order By: Relevance
“…On the other hand, we did not observe any difference between the age of the subjects and the SUS score (satisfaction). All these results are in line with previous research [ 19 , 20 , 25 , 26 ]. Indeed, younger users are more effective (eg, Jones and Caird's glucometer [ 25 ]) and efficient (eg, Mykityshyn et al's glucometer [ 26 ] and Van der Vaart et al's application for narcoleptics [ 20 ]) compared to older users, with a positive and medium correlation [ 20 ].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…On the other hand, we did not observe any difference between the age of the subjects and the SUS score (satisfaction). All these results are in line with previous research [ 19 , 20 , 25 , 26 ]. Indeed, younger users are more effective (eg, Jones and Caird's glucometer [ 25 ]) and efficient (eg, Mykityshyn et al's glucometer [ 26 ] and Van der Vaart et al's application for narcoleptics [ 20 ]) compared to older users, with a positive and medium correlation [ 20 ].…”
Section: Discussionsupporting
confidence: 93%
“…Younger subjects appeared to be more comfortable than older subjects. Jones and Caird [ 25 ] examined the use of a blood glucose meter and found that younger subjects had fewer difficulties and made fewer errors (ie, were more effective) than older subjects. Mykityshyn et al [ 26 ] also examined the use of a glucometer and found that young subjects were faster (ie, more efficient) than older subjects, regardless of the instruction format provided (written and drawn vs video).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We propose below a nonexhaustive analysis focusing on user characteristics that influence usability results (Figure 1). These four main variables are age [3,4,24,25,[29][30][31][32], experience in IT [3,24,32,33], health literacy [29,31,37,38], and motivation [34][35][36]. For instance, a study by Loorbach et al [50] showed that more motivating manual instructions improved effectiveness and efficiency (but not satisfaction) in relation to a mobile phone in an elderly (age 60-70 years) population.…”
Section: Usability and User Characteristicsmentioning
confidence: 99%
“…• Age: young users outperform older users [3,4,24,25,[29][30][31][32] • Experience in information technology (IT) (or technophilia), that is, previous experience in computer and medical devices: technology experts outperform novices [3,24,32,33] • Motivation: more motivated users outperform less motivated users [34][35][36] • Health literacy: users with high levels of health literacy outperform users with low levels of health literacy [29,31,37] With regard to the relationships between these above-mentioned characteristics and usability, there are only few studies examining the link between health [29,31,37,38] or eHealth literacy [29], particularly prior health knowledge, and usability.…”
Section: Introductionmentioning
confidence: 99%